Dissociation and Reconstitution of the Transcriptase and Template Activities of Vesicular Stomatitis B and T Virions - Emerson, Suzanne U. (1972)
Transcriptase activity was dissociated from vesicular stomatitis virions by highionic-strength buffer containing Triton X-100. Considerable enzyme activity could be restored by recombining inactive sedimentable and nonsedimentable virion fractions. Reconstituted transcriptase activity was dependent on the presence of all four nucleoside triphosphates and the concentration of heat-labile molecules in both supernatant and pellet fractions. Lower NaCl concentrations removed ∼46% of virion protein, but did not release transcriptase activity from the pellet fraction, nor could incorporation of (3)H-uridine-5′-triphosphate by complete virions be increased by adding soluble transcriptase. Evidence that the virion nucleocapsid is the transcription template was provided by finding that the pellet contained predominantly virion core nucleoprotein, ribonucleic acid, and homogeneous nucleocapsid coils when viewed by electron microscopy. Removal of envelope G and M proteins by Triton and low-salt buffer without decreasing nucleocapsid polymerase activity indicates that neither G nor M protein is necessary for transcription. Additional data are required to determine whether the minor nucleocapsid proteins L or NSl, or both, which are at least partially solubilized in high-salt buffer, are the transcriptase. Preliminary data suggest that the major N nucleoprotein, which was not solubilized by high-salt buffer, is also required for transcription. Defective T virions contained at least as much transcriptase per weight as did B virions, as determined by restoration with T supernatant fluids of transcription function to B nucleocapsid template. However, the T nucleocapsid would not serve as template for B or T transcriptase, a finding which is interpreted as evidence of T template defectiveness. The presence of defective T nucleocapsids did not interfere with B or T transcriptase function reconstituted with B template.